SISTEM PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI KAMPUS UIN WALISONGO SEMARANG - Usfiyatul Marfu'ah; Siti Rofi'ah; Maksun Maksun (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Prevention and handling of sexual violence in universities is an important things needed. This is related to the high number of cases of sexual violence in universities. Meanwhile, there is no significant implementation of cases of sexual violence in universities. This paper is in order to answer the void regarding the prevention and handling system of sexual violence on campus through regulations and policies implemented by universities. This paper is based on the result of research at the Walisongo Islamic State University in Semarang using descriptive qualitative methods which in extracting data using focus group discussion (FDG), in-depth interviews, and document studies. The results of the study show that: first, the code of ethics becomes an alternative regulation for handling sexual violence on campus as long as there is no regulation on handling sexual violence, although in fact the code of ethics does not contain comprehensively regarding the prosecution of sexual violence cases on campus. Second, campus-owned service institutions that can be used to assist victims of sexual violence are still not optimal and have not been well integrated with the center for gender and child studies (PSGA). Third, the facilities, infrastructure, and space on campus have not supported the creation of a friendly campus with a gender perspective. Fourth, cooperation between leaders and stakeholders in the campus environment is important in creating a campus that is friendly and safe from sexual violence. From these results it can be concluded that in order to create a campus that is safe from sexual violence, an integral effort is needed, both from the leadership commitment, the performance of each unit, as well as public awareness in the campus environmen